2022
DOI: 10.1021/acsami.2c02329
|View full text |Cite
|
Sign up to set email alerts
|

Pd/PdO Electrocatalysts Boost Their Intrinsic Nitrogen Reduction Reaction Activity and Selectivity via Controllably Modulating the Oxygen Level

Abstract: The electrocatalytic nitrogen reduction reaction (eNRR) is regarded as promising sustainable ammonia (NH3) production alternative to the industrial Haber–Bosch process. However, the current electrocatalytic systems still exhibit a grand challenge to simultaneously boost their eNRR activity and selectivity under ambient conditions. Herein, we construct Pd/PdO electrocatalysts with a controlled oxygen level by a facile electrochemical deposition approach at different gas atmospheres. Theoretical calculation resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…These results indicate that the Ni 3 S 2 nanosheets sprouted from the NF bond with Pd 4 S tightly and the formed Pd 4 S-Ni 3 S 2 electrode material can transfer the electrons to the electrolyte quickly during the HER process. Figure f presents the hydrogen generation amount of the Pd 4 S-Ni 3 S 2 /HPNF sample pushed by a j 10 and the reactive rate of H 2 production is about 11.25 mmol/h, which is far superior to the engineered electrode materials listed in Table S7, including the advanced Fe 17.5% -Ni 3 S 2 /NF (0.912 mmol/h), CoS/Ni 3 S 2 -FeS/PNFF (0.65 mmol/h), and (FeCoNi) 9 S 8 -MoS 2 (0.37 mmol/h) catalytic systems. Noticeably, the measured generation amount of H 2 nearly equals to the theoretical value, indicating that the near 100% Faraday efficiency has been achieved for the Pd 4 S-Ni 3 S 2 /HPNF electrocatalyst …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These results indicate that the Ni 3 S 2 nanosheets sprouted from the NF bond with Pd 4 S tightly and the formed Pd 4 S-Ni 3 S 2 electrode material can transfer the electrons to the electrolyte quickly during the HER process. Figure f presents the hydrogen generation amount of the Pd 4 S-Ni 3 S 2 /HPNF sample pushed by a j 10 and the reactive rate of H 2 production is about 11.25 mmol/h, which is far superior to the engineered electrode materials listed in Table S7, including the advanced Fe 17.5% -Ni 3 S 2 /NF (0.912 mmol/h), CoS/Ni 3 S 2 -FeS/PNFF (0.65 mmol/h), and (FeCoNi) 9 S 8 -MoS 2 (0.37 mmol/h) catalytic systems. Noticeably, the measured generation amount of H 2 nearly equals to the theoretical value, indicating that the near 100% Faraday efficiency has been achieved for the Pd 4 S-Ni 3 S 2 /HPNF electrocatalyst …”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, we have also explored the HER performance of Pd 4 S-Ni 3 S 2 /HPNF in an acidic medium (Figure S15, 0.5 M H 2 SO 4 ). The corresponding overpotential is about 96 mV at S7, including the advanced Fe 17.5% -Ni 3 S 2 /NF (0.912 mmol/ h), 42 CoS/Ni 3 S 2 -FeS/PNFF (0.65 mmol/h), 14 and (FeCo-Ni) 9 S 8 -MoS 2 (0.37 mmol/h) 49 catalytic systems. Noticeably, the measured generation amount of H 2 nearly equals to the theoretical value, indicating that the near 100% Faraday efficiency has been achieved for the Pd 4 S-Ni 3 S 2 /HPNF electrocatalyst.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…DFT calculations were conducted to unravel the origin of the improved electrocatalytic NRR performance of FeÀ Fe 3 O 4 . The Gibbs free energy (ΔG) diagram (Figure 6) of NRR on Fe(110), Fe 3 O 4 (311) surfaces, and the oxygen vacancy site of Fe 3 O 4 (311) surface (subsequent to being abbreviated as Fe 3 O 4 (311)_OV site) was constructed based on the associative distal route mechanism which has been proved to be energetically superior to the alternative route in several metal oxides and metal systems, [60][61][62] and the corresponding intermediate structures of NRR on these three surfaces are also displayed in Figure S18-S20. No absorption of N 2 H 4 that is an intermediate in the alternating route of NRR has been detected in the UV/Vis spectra of the electrolytes stained with the p-C 9 H 11 NO indicator after NRR electrolysis (Figure S8), indicating the NRR reaction also occurred in our FeÀ Fe 3 O 4 catalyst by the distal route mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…[99] Other operando spectroscopic techniques including Raman spectroscopy and XRD have been utilized to identify active sites and the reaction mechanisms for the ENRR on different catalysts. [101][102][103][104][105][106][107] Combined with other ex situ and in situ characterization results, the V 4 + site was demonstrated to be responsible for the high ENRR performance on VS 2À x catalysts. [106] The direct observation of electric double layer region on TMN catalysts using different operando spectroscopic techniques can help identify the possible reaction intermediates, solvent and cation effects, reaction mechanisms, and thus guide the optimization of electrocatalysts and electrolytes.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of N 2 H y as the reaction intermediates by SERIAS indicated that the ENRR on Au surfaces follows the associative mechanism [99] . Other operando spectroscopic techniques including Raman spectroscopy and XRD have been utilized to identify active sites and the reaction mechanisms for the ENRR on different catalysts [101–107] . Combined with other ex situ and in situ characterization results, the V 4+ site was demonstrated to be responsible for the high ENRR performance on VS 2− x catalysts [106] .…”
Section: Discussionmentioning
confidence: 99%